Moderating influence of gender on the link of spiritual and emotional intelligences with mental health among adolescents - Shabani, Jafar; Hassan, Siti Aishah; Ahmad, Aminah; Baba, Maznah (Marsland Press, 2011)
This study examined whether, Spiritual Intelligence (SI) and Emotional Intelligence (EI) can be considered as predictor for Mental Health (MH). Also, this study explored the moderating effects of gender on the link between SI and EI with MH among high school students. The participants in the study were 247 high school students, (124 male and 123 female, in the age range between 14-17 years old) at the Gorgan City, north of Iran. The research design was an ex post facto and tested the alternative hypotheses. Three valid and reliable instruments were used to assess SI, EI and MH. Descriptive statistics, multiple and moderated regression analysis were used to analyses the data. The result demonstrated that MH can be influence by SI and EI. In addition, the moderating effect of gender on the relationship of SI and EI with MH was not established.